KOMPOSISI MUSIK BADONDONG BAIBO DALAM MUSIK INSTRMENTAL - Ferry Herdianto; Yusnelli Yusnelli; Freddy Antara (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2021)
The composition of instrumental and vocal music in this creation came from the art of badondong baibo and was developed into an instrumental music performance in the form of a musical composition with an orchestra format. The principle of the formulation of the creation of conventional music science. While the purpose of this creation is 1) to create badondong baibo art with different contexts and functions into modern music compositions and develop it using conventional techniques, 2) to realize musical ideas inspired by badondong baibo art and make it a new musical composition. . While the method of creation is carried out in three stages, namely; 1) data collection stage, 2) creation stage and 3) evaluation stage. This composition can be concluded that; a) creating musical compositions derived from regional arts has its own difficulties, where the creator must understand and explore the arts of the area, b) badondong is a new musical composition that is adapted from the melodies and vocals of badondong baibo in the Danto area of East Kampar district, c) the tone of the composition this music is a modified